2020
DOI: 10.1038/s41589-020-0498-9
|View full text |Cite
|
Sign up to set email alerts
|

d-Cycloserine destruction by alanine racemase and the limit of irreversible inhibition

Abstract: Summary The broad-spectrum antibiotic d -cycloserine (DCS) is a key component of regimens used to treat multi- and extensively drug-resistant tuberculosis. DCS, a structural analogue of d -alanine, binds to and inactivates two essential enzymes involved in peptidoglycan biosynthesis, alanine racemase (Alr) and d -Ala: d -Ala ligase. Inactivation of Alr is thought to proceed via a mechanism-based irreversible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 38 publications
1
39
0
Order By: Relevance
“…33 and 34 ) or the cAMP analogue, dibutyryl-cAMP, analogue which is less hydrophobic than cAMP and is therefore able to pass through cell membranes, where it accumulates intracellularly as mono-butyryl-cAMP. 35 37 Further, as one of the pathway is the synthesis of the precursor of peptidoglycan, one could investigate the antimicrobial susceptibility of M. tuberculosis Δc rp to antimicrobials such as d -cycloserine which targets alanine racemase and d -alanine ligase 38 and vancomycin which binds the d -Ala- d -Ala terminal of the growing peptide chain. 39 Based on the data presented here, we can anticipate an increase in susceptibility of M. tuberculosis Δc rp compared to the parental strain.…”
Section: Discussionmentioning
confidence: 99%
“…33 and 34 ) or the cAMP analogue, dibutyryl-cAMP, analogue which is less hydrophobic than cAMP and is therefore able to pass through cell membranes, where it accumulates intracellularly as mono-butyryl-cAMP. 35 37 Further, as one of the pathway is the synthesis of the precursor of peptidoglycan, one could investigate the antimicrobial susceptibility of M. tuberculosis Δc rp to antimicrobials such as d -cycloserine which targets alanine racemase and d -alanine ligase 38 and vancomycin which binds the d -Ala- d -Ala terminal of the growing peptide chain. 39 Based on the data presented here, we can anticipate an increase in susceptibility of M. tuberculosis Δc rp compared to the parental strain.…”
Section: Discussionmentioning
confidence: 99%
“…231,232 An important inhibitor of alanine racemase is D-cycloserine, a natural product used in the treatment of drug resistant tuberculosis. 233,234 It is notable that the biosynthetic pathway for D-cycloserine contains a reaction catalysed by a racemase, O-ureidoserine racemase 46 (vide supra, Scheme 10A). D-Cycloserine 93 is a relatively non-specific antibiotic and targets M. tuberculosis alanine racemase and D-Ala-D-Ala ligase.…”
Section: Plp-dependent Racemasesmentioning
confidence: 99%
“…As there are significant similarities in the structures of MurC and MurD/ MurE and MurF, it should be possible to design inhibitors that can inhibit the Mur enzymes simultaneously (Kouidmi et al, 2014). Still within the cytoplasm, alanine racemase (Alr) catalyzes the conversion of L-alanine to D-alanine which is required to synthesize the peptide component of Lipid II (De Chiara et al, 2020). There are currently several commercial antibiotics targeting Alr (see Table 1), including D-cycloserine (Kim et al, 2003).…”
Section: Peptidoglycan Biosynthesis and Potential Targetsmentioning
confidence: 99%
“…D-Cycloserine has been used to treat pulmonary and extra-pulmonary TB, including MDR-TB, but this is hampered by severe toxic side-effects (Azam et al, 2016). Recently, it was shown that Alr activity remains detectable in Mtb exposed to clinically relevant D-cycloserine concentrations (Prosser and De Carvalho, 2013;De Chiara et al, 2020). This is due to reversible binding via D-cycloserine-adduct hydrolysis thus enabling dissociation and structural rearrangement within the active enzyme to regain activity.…”
Section: Peptidoglycan Biosynthesis and Potential Targetsmentioning
confidence: 99%
See 1 more Smart Citation